Intra-annual stem radius growth and cell formation of two diffuse-porous tree species in a subtropical forest in Southwest China - Zhang, Yi Xue; Fu, Pei Li; Yan, Qiao Shun; Bräuning, Achim; Fan, Ze Xin (Tree Physiology, 2025)
Studying tree growth and xylem formation is essential for understanding tree resilience to extreme droughts, which are expected to intensify with climate warming. However, researches on intra-annual stem growth and xylogenesis remain limited, particularly in moist subtropical forests. This study monitored the intra-annual stem radius growth and xylem formation of two diffuse-porous tree species, Stewartia pteropetiolata W. C. Cheng and Schima noronhae Reinw. ex Blume, in a subtropical evergreen broadleaved forest in Southwest China, using high-resolution dendrometer measurements for recording stem growth and micro-coring for xylem formation. We analyzed the seasonal patterns of stem radius growth and xylem formation and their responses to seasonal climate variability. Our results revealed that S. noronhae, found at lower elevations, exhibited a later onset of stem growth and xylogenesis, developing wider vessels with thinner walls during a longer enlarging phase. In contrast, S. pteropetiolata, which is distributed at higher elevations, produced smaller vessels with thicker walls during a longer cell-wall thickening phase. Both species showed high relative growth rates under conditions of high temperatures and low vapor pressure deficit. More specifically, S. noronhae maintained higher relative growth rates under a narrower range of favorable temperature and soil water conditions during the rainy season, while S. pteropetiolata sustained growth for a longer growth period in colder and drier conditions. These findings enhance the understanding of angiosperm wood cell kinetics and the eco-physiological response of diffuse-porous trees to climate change in moist subtropical forests.
CRIS-Team Scopus Importer:2025-04-04
Keywords: dendrometer; intra-annual growth; seasonality; subtropical evergreen forest; vessels; xylogenesis